2010
DOI: 10.1007/s12098-010-0150-x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report on Neonatal Screening for Congenital Hypothyroidism, Congenital Adrenal Hyperplasia and Glucose-6-Phosphate Dehydrogenase Deficiency: A Chandigarh Experience

Abstract: Preliminary data on prevalence of various genetic disorders viz. G-6-PDD, CH and CAH in the population of this region revealed that G-6-PDD is most prevalent disorder followed by CH and CAH. More efforts need to be undertaken to create awareness and emphasis on significance of preventive testing to make screening a successful program in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 15 publications
1
39
1
Order By: Relevance
“…However homozygous female with G6PDD can present clinically [18]. Kaur etal reported the incidence of G6PDD in this study was found to be 1 in 112 (0.89%) with a higher prevalence in males than females in Chandigarh, India which was true for the present study also [19].Pao M et al conducted a retrospective hospital based study among 2479 neonates and observed G6PDD incidence to be 2%. In males, incidence was 2.83 % and in females incidence was 1.05% [10].Kumar P et al performed a meta-analysis in both fixed and random effect models.…”
Section: Male To Female Ratiosupporting
confidence: 67%
“…However homozygous female with G6PDD can present clinically [18]. Kaur etal reported the incidence of G6PDD in this study was found to be 1 in 112 (0.89%) with a higher prevalence in males than females in Chandigarh, India which was true for the present study also [19].Pao M et al conducted a retrospective hospital based study among 2479 neonates and observed G6PDD incidence to be 2%. In males, incidence was 2.83 % and in females incidence was 1.05% [10].Kumar P et al performed a meta-analysis in both fixed and random effect models.…”
Section: Male To Female Ratiosupporting
confidence: 67%
“…Devi AR and Noushad et al, [8], has taken the following range for comparison -CBTSH value < 10µ/ml as normal,10-20 µU/ml as borderline and > 20 µU/ml as abnormal. Recently,another study from India by Gurjit Kaur et al, [9] from Chandigarh has taken 9µU/ml as the TSH cutoff value. Ruth V Mikelsaar et al, [10] from Estonia have taken the TSH cut -off value for neonatal screening as 12 µU/ml,which is a still lower cut-off value as compared to our study.…”
Section: Discussionmentioning
confidence: 99%
“…(Foroughinia and Karimi, 2007;Kaur et al, 2010;Kuwahata et al, 2010;Parashar, 2010) was put forth. One main reason contributing to the severity of this disease is the fact that acute hemolysis can occur and that it is difficult to prevent the hemolysis caused by accidental intake of drugs.…”
Section: Introductionmentioning
confidence: 99%